Utilização de zebrafish para validação de programa computacional aplicado à análise cardíaca após administração de medicamentos cardiotônicos - Motheo, Stéphanie Ferguson (Universidade Federal de São Carlos, 2020)
The zebrafish (Danio rerio) is a vertebrate widely used as a model for laboratory tests, due to its high fertility, practical handling and low cost. The cardiac characteristics of this species, as well, as the easy absorption of substances present in the water by the tissues of different organs, makes it an excellent model for cardiotoxicity studies. Thus, the present study aims to validate a program (CardioCount v2.0) capable of detecting cardiac changes like, intervals of cardiac contraction and contraction patterns in zebrafish larvae. For this, four substances (dopamine, atropine, adrenaline and haloperidol) were selected, to which zebrafish larvae were exposed in different concentrations. Through filming, the 60 larvae with 96 hpf were anesthetized by immersion of 0.7 M tricaine methanesulfonat, filmed and analyzed for variations in heart rate, entropy and possible cardiotoxicity, with 1% DMSO as control. Tests performed with dopamine showed a significant change in the concentration of 2.5 µM with respect to entropy; in the case of adrenaline, all doses resulted in an increase in HR except for 1.0 µM; with respect to atropine, at the dose of 2.50 µM there was an increase in entropy and, in the test with haloperidol, there was a greater dispersion of effects and a greater dependence on the concentration value, with a decrease in heart rate at doses of 2, 5 and 20 µM and in changing entropy with concentrations of 5, 10 and 20 µM. The analysis based on cardiac frequency and entropy parameters quantified in zebrafish larvae, using the computer program CardioCount v.2.0 allowed to quickly and accurately detect cardiological effects of the following drugs: dopamine, adrenaline, atropine and haloperidol.
Use of zebrafish to validate a computer program applied to cardiac analysis after administration of cardiotonic drugs
Keywords: Coração; Peixe-zebra; Software; Heart; Zebrafish; CIENCIAS BIOLOGICAS